Agricultural and rural transformations in Asian development: Past trends and future challenges - Vos, Rob (United Nations University, 2018)
This paper re-examines Asia’s agricultural and rural transformations in the context of economywide structural change. It will focus on the different pathways Asian societies have taken in terms of agricultural transitions; transformation of food systems with rising incomes and urbanization; infrastructure development to forge rural–urban linkages; and implications of broader structural economic transformations, with the objective of identifying the factors of cumulative causation explaining why development accelerated in one part of the region and lagged in another. In light of the review of evidence presented in this paper, lessons will be drawn as to how to address today’s challenges for the development of Asia’s agriculture and food systems and possible pathways for more inclusive and sustainable rural transformations in the coming decades.